Evaluation of NTCP and Second Cancer Induction from Modulated Arc Therapy for High-Risk Prostate Carcinoma by COUPÔLE Software - Assya Boughalia; Mohamed Fellah; Mohamed Zineddine El Ghribi; Kenza Benacer (Iranian Journal of Medical Physics, 2025)
Introduction: Assessing the toxicity and the risk of radiation-induced secondary cancer is crucial for optimizing treatment planning in prostate carcinoma patients with high risk undergoing Volumetric Modulated Arc Therapy (VMAT). This study aims to evaluate normal tissue complication probability (NTCP) and excess absolute risk (EAR) for different structures (organs at risk, the body). The developed in-house software COUPÔLE was used for toxicity and risk estimation and verified against BIOSUITE. Material and Methods: A cohort of twelve randomly selected patients treated with 76 Gy (2 Gy/fraction) using a 6 MV (ELEKTA) treatments were analyzed. Treatments plans were generated using the MONACO system.NTCPs were calculated for rectal bleeding, fecal incontinence and bladder contracture endpoint, while secondary cancer risks were estimated using differents radiobiological models(the Linear Quadratic (LQ), Schneider Linear Exponential and Plateau model) for  rectum, bladder, and whole body. Results: NTCP values of 6.6% and 5.7% for rectal bleeding and bladder toxicity (COUPÔLE vs. BIOSUITE) and 5.3% and 5.4% for fecal incontinence. No bladder toxicity was observed. The estimated risk for rectum and bladder (LQ model) were 0.06 (0.02-0.15) and 0.01 (0.0-0.03), respectively. Using the Schneider model, whole-body risk reached 5.40% for V50Gy. The risk was notably higher for the rectum than for the bladder, highlighting the need for further optimization. Conclusion: These findings confirm the reliability of COUPÔLE for NTCP and secondary cancer risk estimation, demonstrating its applicability for clinical decision-making in radiation oncology.